Electrochemical and Spectroscopic Study of Pyranine Fluorescent Probe: Role of Intermediates in Pyranine Oxidation - Ureta-Zanartu, M; Aspee-Lamas, A (American Chemical Society, 2011)
8-Hydroxy-1,3,6-pyrenetrisulfonic acid (pyranine) is a hydrophilic pyrene derivative, highly reactive toward free radicals, that has been widely used in methodologies for the evaluation of antioxidant capability and the monitoring of free-radical polymer processes. In this work, we studied and characterized the electrochemical oxidation of pyranine by cyclic voltammetry, chronocoulometry, and spectroelectrochemical techniques. The electrochemical oxidation of pyranine leads to the formation of a pyranine free radical (PyO?) that is easily detectable by spectroelectrochemistry measurements. This oxidation process takes place through a CEC (chemical-electrochemical-chemical) mechanismwhere the chemical step previous to the oxidation corresponds to an acid-base equilibrium. A reversible diffusion-controlled electron-transfer process observed at high pH suggests that the charge-transfer process is followed by a chemical step associated with secondary PyO? dimerization-disproportionation chemical reactions. Surprisingly, pyranine oxidation mediated by peroxyl radicals showed a change in the stoichiometry of the reaction at pH values close to the pKa of pyranine. This behavior was attributed to the different reactivities of the ionized (PyO-) and the nonionized (PyOH) phenolic forms of pyranine for peroxyl radicals, affecting the role of secondary reactions at different pH values and, therefore, the measured stoichiometry. © 2011 American Chemical Society.